STRATEGI PENINGKATAN PENDIDIKAN KARAKTER DI LINGKUNGAN MADRASAH ALIYAH NEGERI PULAU TALIABU - Pardin (Merwin Publisher, 2023)
Thepurpose of this researh is to describ the managemeent of charactter formation programs at the State Islamic Senior High School of Pulau Taliabu. A qualiltative approch with a case study design was employed, conducted at MANi Pulau Taliabu. Data collection methods included observations, interviews, and document examinations, with data analysis involving summarization, presentation, and drawing conclusions. This study found that there are several distinct steps taken to strengthen character, such as observing and learning, cooperating, planning, executing the plan, reviewing it, and assessing how it can be improved. The school principal receives assistance from the team and coordinators. There are four aspects to implementing this plan: applying it in all aspects of the school, ensuring everyone believes in it, setting a real example, and communicating with parents. The school principal also oversees how the plan is implemented. Finally, they assess how well the plan is working, make changes if necessary, and discuss it with others..